Sustainable green practices and knowledge in manufacturing organisations: Hybrid methods from a green dynamic capability approach - Rashed, Md; Hossain, Mohammad Imtiaz; Akter, Tania; Ali, Md Ashraf; Rabbi, Md Fajle; Mamun, Mohammad Abdullah Al (Elsevier B.V., 2026)
As a resource-intensive and polluting industry, the manufacturing sector increasingly relies on sustainable green practices to maintain industrial competitiveness and protect the environment. However, little scholarly attention has been paid to how organisational capabilities lead to sustainable green practices in emerging economies such as Bangladesh. This study examines the associations between green dynamic capability practices and green innovation, as well as the enhancement of sustainable green practices through the mediating role of organisational resilience and environmental dynamism. This study analyses survey data from 287 Bangladeshi manufacturing companies using partial least squares structural equation modelling and fuzzy-set qualitative comparative analysis. These findings indicate that green dynamic capability practices have a direct positive effect on sustainable green practices and an indirect positive effect on green innovation and organisational resilience. Notably, environmental dynamism intensifies these relationships, suggesting that companies operating in more unstable markets must depend on resilience and innovation to achieve green, sustainable outcomes. Theoretically, this study contributes to the green dynamic capabilities theory and connects it with quantifiable sustainable practices. It offers practical advice for manufacturing managers in emerging economies on integrating resilience and innovation into green strategies. This study’s multimethod approach reveals both linear and configurational pathways, providing valuable insights for practitioners, policymakers, and related developing countries to enhance the resilience and sustainability of manufacturing firms in dynamic environments.